2006
DOI: 10.1021/bc050299g
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of C60-Fullerene and Carboxyfullerene with Proteins:  Docking and Binding Site Alignment

Abstract: The unique properties of fullerenes have raised the interest of using them for biomedical applications. Within this framework, the interactions of fullerenes with proteins have been an exciting research target, yet little is known about how native proteins can bind fullerenes, and what is the nature of these interactions. Moreover, though some proteins have been shown to interact with fullerenes, up to date, no crystal structure of such complexes was obtained. Here we report docking studies aimed at examining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 42 publications
(65 reference statements)
7
90
1
2
Order By: Relevance
“…Albumin From four main (highly populated) binding pockets detected for albumin-C 60 model, the lowest energy location stays in an agreement with literature data [31] (see Table 1 and Fig. 4).…”
Section: Binding Sites Analysissupporting
confidence: 87%
See 3 more Smart Citations
“…Albumin From four main (highly populated) binding pockets detected for albumin-C 60 model, the lowest energy location stays in an agreement with literature data [31] (see Table 1 and Fig. 4).…”
Section: Binding Sites Analysissupporting
confidence: 87%
“…Binding sites on HSA for nC 60 occurred similar to these for separate molecules. The same type of binding sites as was reported for interactions C 60 -albumin [31] were experimentally detected in nC 60 -albumin complexes [32]. These observations indicate that even though investigations of separate C 60 molecules are not complete as they should be for nC 60 , they bring reliable results, which can be extended on protein-nC 60 complexes.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…While others have investigated protein-binding techniques using fullerenes, including human serum (11)(12)(13)(14)(15), there is still little information regarding the identification of protein binding interactions. Here, it was demonstrated that TGA interacted with a wide range of proteins in human serum.…”
Section: Discussionmentioning
confidence: 99%